2011
DOI: 10.1371/journal.pone.0014633
|View full text |Cite
|
Sign up to set email alerts
|

Renalase Deficiency in Heart Failure Model of Rats—A Potential Mechanism Underlying Circulating Norepinephrine Accumulation

Abstract: BackgroundSympathetic overactivity and catecholamine accumulation are important characteristic findings in heart failure, which contribute to its pathophysiology. Here, we identify a potential mechanism underlying norepinephrine accumulation in a rat model of heart failure.Methodology/Principal FindingsInitially, we constructed a rat model of unilateral renal artery stenosis (n = 16) and found that the expression of renalase, a previously identified secreted amine oxidase, was markedly reduced in the ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 23 publications
2
64
1
2
Order By: Relevance
“…Nevertheless, it should be emphasized that renalase is secreted not only by the kidney, but also by cardiomyocytes, liver, adipose tissue, skeletal muscles, endothelium, and by the Central Nervous System [27]. Previously, Gu et al [28] reported an increased renalase concentration in HD patients. They hypothesized that in this condition a more activated renalase was synthesized to cope with the increased NA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be emphasized that renalase is secreted not only by the kidney, but also by cardiomyocytes, liver, adipose tissue, skeletal muscles, endothelium, and by the Central Nervous System [27]. Previously, Gu et al [28] reported an increased renalase concentration in HD patients. They hypothesized that in this condition a more activated renalase was synthesized to cope with the increased NA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In another experimental model of CKD on nephrectomised pups, Gosh et al [7] observed higher norepinephrine levels in the CKD model, suggesting its decreased metabolism. Gu et al [28] noticed lower renalase expression in the ischaemic kidney model in comparison to healthy one, suggesting that renal blood flow may affect renalase production. There are also some data concerning renalase concentration in patents with end stage renal disease.…”
Section: Renalase and Kidney Functionmentioning
confidence: 98%
“…Gu et al [28], in the study mentioned in the previous paragraph, besides observing renalase in the CKD model, also created a model of heart failure in rats through the ligation of the left anterior descending coronary artery. This group observed increasing renal renalase expression with the highest level one week after myocardial infarction [28]. There are few clinical studies considering renalase concentration in patients with heart failure.…”
Section: Renalase and Cvdmentioning
confidence: 99%
“…First of all, as mentioned above, renalase 1 was detected in body fluids such as blood plasma and urine [1,10,29,30]. Secondly, in patients suffering from chronic kidney disease and primary glomerulonephritis, as well as in animal model of kidney failure, extracellular renalase was absent or present at lower concentrations, indicating the kidneys as the main source of the secreted protein [1,[30][31][32].…”
Section: Renalase Isoforms and Gene Expression Patternmentioning
confidence: 99%
“…Downregulation of RNLS expression in healthy mice by antisense phosphorothioate oligonucleotides was found to produce both a rise in blood pressure and an increased sensitivity to norepinephrine injection [8,60]. In various rat models of chronic kidney disease, lower concentrations of renalase in kidneys, heart and blood were always accompanied by increased levels of epinephrine and norepinephrine in plasma and heart [30,32,61,62]. Furthermore, some of these studies together with other investigations on rodent models showed that renalase levels inversely correlate with the concentration of dopamine, which has hypotensive and cardioprotective actions at variance with other catecholamines [63], in kidneys and urine [32,64].…”
Section: Nadph-dependent Diaphorase Reactions With Various Artificialmentioning
confidence: 99%